Self‐harm, in‐person bullying and cyberbullying in secondary school‐aged children: A data linkage study in Wales. Issue 1 (9th October 2022) - John, Ann; Lee, Sze Chim; Puchades, Alice; Del Pozo‐Baños, Marcos; Morgan, Kelly; Page, Nicholas; Moore, Graham; Murphy, Simon
Abstract: Introduction: Although the evidence base on bullying victimization and self‐harm in young people has been growing, most studies were cross‐sectional, relied on self‐reported non‐validated measures of self‐harm, and did not separate effects of in‐person and cyberbullying. This study aimed to assess associations of self‐harm following in‐person bullying at school and cyberbullying victimization controlling for covariates. Methods: School survey data from 11 to 16 years pupils collected in 2017 from 39 Welsh secondary schools were linked to routinely collected data. Inverse probability weighting was performed to circumvent selection bias. Survival analyses for recurrent events were conducted to evaluate relative risks (adjusted hazard ratios [AHR]) of self‐harm among bullying groups within 2 years following survey completion. Results: A total of 35.0% (weighted N = 6813) of pupils reported being bullied, with 18.1%, 6.4% and 10.5% being victims of in‐person bullying at school only, cyberbullying only and both in‐person bullying at school and cyberbullying respectively. Adjusting for covariates, effect sizes for self‐harm were significant after being in‐person bullied at school only (AHR = 2.2 [1.1–4.3]) and being both in‐person bullied at school and cyberbullied (AHR = 2.2 [1.0–4.7]) but not being cyberbullied only (AHR = 1.2 [0.4–3.3]). Feeling lonely during recent summer holidays was also a robust predictor (AHR = 2.2 [1.2–4.0]). Conclusions: We reaffirm the role of in‐person bullying victimization on self‐harm. Pupils were twice as likely to self‐harm following in‐person bullying as their nonvictimised peers. Interventions for young people that minimize the potential impacts of bullying on self‐harm should also include strategies to prevent loneliness.